2017
DOI: 10.1186/s12879-017-2346-4
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacteriaceae producing extended-spectrum β-lactamases (ESBLs) colonization as a risk factor for developing ESBL infections in pediatric cardiac surgery patients: “retrospective cohort study”

Abstract: BackgroundChildren with cardiac defects need many hospitalizations and repetitive antibiotic therapies, with an increasing risk of colonization with multidrug-resistant bacteria (MDRB) such as extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-E) Post-operative infections with these bacteria in paediatric cardiac surgery are life threatening. This article aims to study the prevalence of ESBL colonization among paediatric cardiac surgery patients, and to compare occurrence of post-operative infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
14
1
1
Order By: Relevance
“…This finding is consistent with several studies that also identified ESBL-PE colonization as risk factor for ESPL-PE infection. 21,28,[33][34][35] Carbapenem exposure after availability of the screening result differed between patients with a positive screening result and patients with a negative screening result, which is supported by a recent French study that showed much greater carbapenem exposure for ESBL-PE-colonized patients. 28 This difference occurred despite screening not being accompanied by an antimicrobial stewardship intervention; however, the results were available to the treating physicians through the laboratory system and seem to have influenced their prescription strategies.…”
Section: Discussionmentioning
confidence: 78%
“…This finding is consistent with several studies that also identified ESBL-PE colonization as risk factor for ESPL-PE infection. 21,28,[33][34][35] Carbapenem exposure after availability of the screening result differed between patients with a positive screening result and patients with a negative screening result, which is supported by a recent French study that showed much greater carbapenem exposure for ESBL-PE-colonized patients. 28 This difference occurred despite screening not being accompanied by an antimicrobial stewardship intervention; however, the results were available to the treating physicians through the laboratory system and seem to have influenced their prescription strategies.…”
Section: Discussionmentioning
confidence: 78%
“…Targeted strategies designed to cope with the challenge of ESBL-PE are needed. Since a majority of infections are preceded by colonisation [ 18 20 ] knowledge of the duration of colonisation with ESBL-PE after travel could influence recommendations regarding management of gram-negative infections. In this respect, knowledge of the resistance profiles of travel-associated ESBL-PE and any change in resistance rates during prolonged colonisation, would also be of interest.…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted here, hospital management without bacteriological services is no longer an option. It is always unfortunate when the level of advanced and device-dependent medical care is not balanced against the institutions’ ability to record and manage problems that follow advanced medical care [51]. In health care settings where non-fermenters and other contaminants are constantly sought for and immediately removed whenever found, any co-existence between Enterobacteriaceae and non-fermenting bacteria would be occasional and of short duration.…”
Section: Discussionmentioning
confidence: 99%